Jazz: uma proposição para criação na Escola de Dança Paula Lisboa - VALE, Mayara Almeida do (2018)
This Conclusion of course's work is about my history in Dance, how and what influences led me to the Hybrid creation in the Jazz dance's language, searching a proposal of teaching with focus on possibilities of development of the body's consciousness to discover new movements and creating process. The objective of this work is discussing the Jazz dance as hybrid's language relating with a proposal of teaching for the creation of selfsame. Your methodology constitutes about data collection and from observations, what resulting in the choreographic collective suggestion of my students of the Dancing School Paula Lisboa. the notion of hybridization in this work is understood from Nestor Canclini (2008) what starts e keeps present in all the development of this research and my propositions begins of a knowledge about the book of Lenira Rengel (2008), "Temas de movimento de Rudolf Laban". This research demands add to the making of creative propositions, thinking in the Jazz dance as hybrid language and in constantly changing.